Postpartum gestational diabetes insipidus related to preeclampsia: A case report - Alisa Goldrich; Jessica Yuan; Hindi Stohl (Case Reports in Women's Health, 2023)
Gestational diabetes insipidus (GDI) is a rare complication of pregnancy thought to be due to increased vasopressinase produced by the placenta. It typically occurs at the end of the second or in the third trimester. This report describes a case of GDI diagnosed postpartum in the setting of newly diagnosed superimposed preeclampsia. A 39-year-old Hispanic woman (gravida 2 para 2) presented ten days postpartum with a persistent headache and elevated blood pressures in the setting of a history of chronic hypertension, meeting criteria for superimposed preeclampsia. Repeat lab work was notable for mild elevation of liver function enzymes. Despite normalization of blood pressures, her headache persisted and further workup revealed polyuria, suspected to be vasopressinase-induced diabetes insipidus. The patient was started on oral desmopressin with improvement of polyuria and symptoms.